The Transformation of the Family Institution in the Modern Russian and Mongolian Society: The Structural and Functional Features - Vinokurova, Anna Viktorovna; Badaraev, Damdin Dorzhievich; Badmatsyrenov, Timur Batorovich (International Review of Management and Marketing, 2016)
The article deals with the main trends in the transformation of the social institution of the family in the conditions of modern Russian and Mongolian society from the standpoint of structural-functional approach. The main attention is paid to the social environment characteristic of the factors contributing to changes in the specific functions of the family, first of all, reproductive. The study of this problem was carried out on the basis of an integrative research strategy, including the primary (the results of an empirical study of the regional social welfare and well-being of families living in Primorskiy Krai) and secondary analysis (results of the studies of Russian and Mongolian authors, as well as statistical data). A comprehensive analysis made by us showed that in the Russian and Mongolian society the family acts as a basic value of life. At the same time it was found that Russian and Mongolian families experiencing difficulties of social and economic nature, adversely affecting on the realization of their specific functions, especially reproductive. On the one hand, the effective functioning of the families is difficult under the influence of not very favorable material and domestic living conditions of much of the population of modern Russia and Mongolia. On the other hand, focus on achieving a certain standard of living standards requires considerable resources and economical housekeeping. All this determines a decrease the number of members in the family, since the formation of plants on welfare due to internal material resources leads to a conscious restriction of the number of children. Keywords: social institution, the family, the structural and functional approach, reproductive function, social well-being, social transformation, Mongolia. JEL Classifications: I310, I380, Z130